2023
DOI: 10.1038/s41598-023-38692-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural resveratrol analogs differentially target endometriotic cells into apoptosis pathways

Abstract: The specific characteristics of endometriotic cells are their ability to evade the apoptotic machinery and abnormal response to apoptotic stimuli. Natural-originated compounds may constitute a beneficial strategy in apoptosis modulation in endometriosis. We investigated and compared the potency of natural resveratrol analogs, including piceatannol, polydatin, and pterostilbene, in targeting cell death pathways, including apoptosis-related morphologic and biochemical processes, alongside the modulation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Caution is also needed while choosing the preferable dose, as lower doses of resveratrol were reported as anti-apoptotic and higher as pro-apoptotic due to the effect on SIRT1 and p53 [87]. Differences were also observed regarding the cell type, with endometriotic cells being more prone to apoptosis at higher concentrations of resveratrol (>100 µM) than endometrial [197].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caution is also needed while choosing the preferable dose, as lower doses of resveratrol were reported as anti-apoptotic and higher as pro-apoptotic due to the effect on SIRT1 and p53 [87]. Differences were also observed regarding the cell type, with endometriotic cells being more prone to apoptosis at higher concentrations of resveratrol (>100 µM) than endometrial [197].…”
Section: Discussionmentioning
confidence: 99%
“…It also induced dosedependent DNA fragmentation and caspase-3 and caspase-7 activity. ESCs were observed to be more resistant to its effect at higher concentrations (100,200, 400 µM) compared with 12Z cells [197]. Another study by Zou et al explored the effect of resveratrol on ectopic ESCs, where they showed that resveratrol promoted oxidative stress and inhibited the proliferation and migration of ESCs due to ferroptosis [181], a non-apoptotic, irondependent cell death.…”
Section: Cell Modelsmentioning
confidence: 99%
“…RSV is known for its anticancerous properties, mediating apoptosis, cell growth, metastasis, and angiogenesis, as illustrated in Figure 2 [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Its mechanism involves reducing angiogenesis and increasing apoptosis through the inhibition of vascular endothelial growth factor (VEGF) expression by downregulating hypoxia-inducible factor 1 (HIF-1) [ 76 , 77 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…MCF-7 and MDA-231 (cancerous cell lines), along with MCF-10 and skin fibroblast HDFa (non-cancerous cell lines), were seeded at a density of 1x10 4 cells per well in 96-well Clear Flat Bottom Polystyrene TC-Treated plates using a 1 × 8 Stripwell™ format. The cells were cultured in their respective media to a final volume of 100 µL/well ( Gołąbek-Grenda et al, 2023 ). The cancerous cell lines were cultured in Dulbecco's Modified Eagle Medium (DMEM), supplemented with fetal bovine serum (FBS) or bovine calf serum (BCS), antibiotics (penicillin–streptomycin), and glutamine.…”
Section: Assessment Of Wheatgrass Methanol Extract Cytotoxicity On Br...mentioning
confidence: 99%